👤
YzefeeR
a fost răspuns

3x(2x-3) + (x-5)(3-2x) raspuns rapid va rog sunt la teza


Răspuns :

3x(2x-3) + (x-5)(3-2x)=6x²-9x+3x-6x²-15+10x=4x-15
3x(2x-3) + (x-5)(3-2x) = 0
6x² - 9x + 3x - 15 - 2x² + 10x = 0
4x² + 4x - 15 = 0

[tex]x_1 = \frac{-4 + \sqrt{ 4^{2}+4*4*15}}{2*4}=\frac{-4+\sqrt{16+240}}{8}=\frac{-4+\sqrt{256}}{8}= \\ \\ =\frac{-4+16}{8}=\frac{12}{8}=\frac{3}{2} \\ \\ x_2 = \frac{-4 - \sqrt{ 4^{2}+4*4*15}}{2*4}=\frac{-4-\sqrt{16+240}}{8}=\frac{-4-\sqrt{256}}{8}= \\ \\ =\frac{-4-16}{8}=\frac{-16}{8}=-2 [/tex]